El desarrollo psicomotriz en los niños con deficiencias auditivas del Instituto de educación especial de ciegos y sordos de la cuidad de Machala año lectivo 2013-2014 - Sánchez Ramos, Johanna del Carmen (2015)
This research is of vital educational importance and fundamental to the deployment of the drive to children, since the natural energy that have forced to be in constant motion, so it is necessary to use that motor action and to channel it positively in performing motor exercises, as well as mental and consents representing a client, allowing you to acquire sensory experiences as a basis for the formation of notional concepts, thus contributing to the development of cognitive functions.In this institution the right methodology when working with children with hearing impairments, by the lack of knowledge on teachers for proper implementation and lack of update on the subject, causing weaknesses in training students are not within of this prestigious institution.The theoretical concepts expressed serves to support this research, which focuses on the exposed scientifically variables such as physical engine and hearing impairments, which guide us about the effects of the application of motor activities and the use of an appropriate methodology and implementation of teaching materials in performing motor and auditory exercises that promote the integral development of the freshman. In order for improved teaching-learning process in this institution, and to pioneer application of technological resources in classes. While at the same academic level as large academic institutions in other major cities of Ecuador.